Health inequalities and health equity challenges for victims of modern slavery. (2nd November 2018) - Dando, Coral J; Brierley, Robin; Saunders, Karen; Mackenzie, Jay-Marie
Abstract: Background: Modern slavery is a serious organized crime, with severe consequences for the physical and mental health of victims, and so has public health implications. Anecdotally many victims of sex slavery experience difficulties accessing healthcare. Public Health England recently articulated the importance of health engagement to address modern slavery but little is known about the experiences of the survivors. Methods: We conducted in depth interviews with Albanian female survivors of sex slavery who all displayed significant and complex health needs. Interviews were conducted between July 2017 and January 2018. Thematic analysis identified four primary themes: (i) barriers to access, (ii) negotiating access, (iii) health needs and care received and (iv) overall experience of primary care. Results: Survivors experienced repeated challenges accessing healthcare, for themselves and their children, and initially could not access GP services. When accompanied by an advocate they reported qualitatively and quantitatively improved experiences resulting in improved permeability. Confusion surrounding eligibility criteria and a lack of understanding of modern slavery emerged as the primary barriers, fueling biased adjudications. Conclusions: The importance of advocates, enabling rights-based approaches, improving understanding about access to health services for vulnerable groups, and a need for education across health service settings are discussed.